Promoting digital health equity through remote patient monitoring: A feasibility study. Issue 28 (1st October 2022) - Kessler, Alaina J.; Besculides, Melanie; Kisswany, Carol; Liu, Mark; Berkalieva, Asem; Mazumdar, Madhu; Smith, Cardinale B.; Gorbenko, Ksenia O.
Abstract : 441 Background: Remote patient monitoring (RPM) is a form of telemedicine involving collection and transmission of health data from patients to providers using non-invasive digital technology. RPM may offer earlier recognition of clinical deterioration to help reduce acute care use and improve healthcare outcomes. Studies of digital interventions in oncology have demonstrated reduction in symptom distress and unplanned hospitalizations but lack focus on minority patients. Studies of telehealth aiming to address disparities have not focused on patients with cancer. In this pilot study, we evaluated the feasibility of RPM among patients with cancer at a large urban medical center serving a racially and socioeconomically diverse population. Methods: We partnered with Current Health to provide an FDA-approved RPM wearable device, which included a secure HIPAA-compliant platform, to collect heart rate, temperature, respiration, oxygen saturation, and blood pressure. The kit included broadband access and a tablet to provide telehealth services. Oncology coordinators determined clinical inclusion and exclusion criteria of RPM initiation for patients. A centralized team of Nurse Practitioners (NPs) monitored alarms. Clinical alarms indicated abnormal vital signs; technical alarms indicated no data transmission for a 12-hour period. We measured feasibility by recruitment and retention, and used descriptive statistics to describe the study population, time enrolled on RPM, and alarms. Results: To date, we enrolled 39 patients on the RPM platform over a 14-month period with a weekly census of 10 patients undergoing RPM monitoring. Of the 39 patients, 19 (49%) were white, 10 (26%) Black, and 5 (13%) Asian; 3 (8%) patients identified as Hispanic. Nine (23%) patients had either primary or secondary Medicaid insurance. The average age was 57.9 years. The majority of patients (95%) had hematologic malignancies, all of whom were enrolled on hospital discharge. The mean length of time per patient enrolled with the device was 21.7 days. Over 14 months, there were 607 technical and 118 clinical alarms with an average of 2 clinical alarms per week addressed by NPs by phone, indicating low clinician burden. Conclusions: This pilot study demonstrated the feasibility of RPM in patients with cancer at home. Future studies should focus on equity-driven implementation of RPM in patients with cancer, as well as patient-reported and healthcare utilization outcomes to identify best practices in telemedicine implementation. RPM has promise to deliver high quality and equitable cancer care.